Introduction [to Encoding motion: Case studies from Africa] - (:unkn) unknown (My University, 2007)
Introduction to the Special Issue "Encoding motion: Case studies from Africa. In memory of Ursula Drolc", edited by Angelika Mietzner & Yvonne Treis
Keywords: African Research